Unique foot posture in Neanderthals reflects their body mass and high mechanical stress. Issue 161 (December 2021) - Sorrentino, Rita; Stephens, Nicholas B.; Marchi, Damiano; DeMars, Lily J.D.; Figus, Carla; Bortolini, Eugenio; Badino, Federica; Saers, Jaap P.P.; Bettuzzi, Matteo; Boschin, Francesco; Capecchi, Giulia; Feletti, Francesco; et al.
Abstract: Neanderthal foot bone proportions and morphology are mostly indistinguishable from those of Homo sapiens, with the exception of several distinct Neanderthal features in the talus. The biomechanical implications of these distinct talar features remain contentious, fueling debate around the adaptive meaning of this distinctiveness. With the aim of clarifying this controversy, we test phylogenetic and behavioral factors as possible contributors, comparing tali of 10 Neanderthals and 81 H. sapiens (Upper Paleolithic and Holocene hunter-gatherers, agriculturalists, and postindustrial group) along with the Clark Howell talus (Omo, Ethiopia). Variation in external talar structures was assessed through geometric morphometric methods, while bone volume fraction and degree of anisotropy were quantified in a subsample ( n  = 45). Finally, covariation between point clouds of site-specific trabecular variables and surface landmark coordinates was assessed. Our results show that although Neanderthal talar external and internal morphologies were distinct from those of H. sapiens groups, shape did not significantly covary with either bone volume fraction or degree of anisotropy, suggesting limited covariation between external and internal talar structures. Neanderthal external talar morphology reflects ancestral retentions, along with various adaptations to high levels of mobility correlated to their presumably unshod hunter-gatherer lifestyle. This pairs with their high site-specific trabecular bone volume fraction and anisotropy, suggesting intense and consistently oriented locomotor loading, respectively. Relative to H .sapiens, Neanderthals exhibit differences in the talocrural joint that are potentially attributable to cultural and locomotor behavior dissimilarity, a talonavicular joint that mixes ancestral and functional traits, and a derived subtalar joint that suggests a predisposition for a pronated foot during stance phase. Overall, Neanderthal talar variation is attributable to mobility strategy and phylogenesis, while H. sapiens talar variation results from the same factors plus footwear. Our results suggest that greater Neanderthal body mass and/or higher mechanical stress uniquely led to their habitually pronated foot posture.